Geologic reconnaissance of the island of Velika Palagruža (central Adriatic, Croatia) - Korbar, Tvrtko (Array, 2009)
Summary: Velika Palagruža (Pelagosa) is the largest island of the Palagruža archipelago (central Adriatic Sea, Croatia). Despite its minute size the island bears a certain geological interest being the only exposed piece of land in the central part (Mid-Adriatic ridge) of the common Adriatic foreland of the Apenninic and the Dinaridic orogenic domains. The litho-, bio-, and chemostratigraphic (strontium and sulphur isotopes) characteristics of the sedimentary units, along with tectono-structural and geomorphic characteristics of the island, are described in this paper. The oldest Žalo unit is composed of highly deformed siliciclastics containing gypsum, and carbonates of Middle Triassic (Ladinian) age. This unit represents a transitional fl uvial-to-shallow marine, occasionally evaporitic environment, typical of the Middle Triassic rifting phase of the Adriatic microplate. Soft and strongly deformed Žalo unit deposits are found along a probably still active, WNW–ESE striking, subvertical, oblique-slip fault that crosses the entire length of the island. The Žalo unit is probably in diapiric contact with the Lanterna unit, poorly defi ned as Late Triassic, and characterized by dolomite with chert and dolomite breccia, presumably deposited in a transitional platform-to-basin environment of an evolving Adriatic basin. The Lanterna unit deposits are capped by Miocene biocalcarenites of the Salamandrija unit over an almost perpendicular discordance, possibly representing an unconformity, suggesting that an early deformational phase preceded a Miocene marine transgression. Talus, landslide deposits, and humic soil make up the cover of the bedrock sedimentary succession, and they represent the ultimate phase of emersion of the island, which probably occurred during Pliocene(?) to Quaternary times. An active neotectonic regime of the central Adriatic is evidenced by present-day seismicity, while r